SISTEM CERDAS UNTUK MEMPREDIKSI CHORDS GITAR DARI LAGU MP3 DENGAN METODE MEL-FREQUENCY CEPSTRAL COEFFICIENTS - Rachmat Hidayat (LPPM Universitas Bina Sarana Informatika, 2010)
This study aims to identify and find the key tone of the song using extraksi cord mp3. An application that serves to extract the key songs on the guitar tune, so that will generate the key (Cord) tone that represents the humming. Technique Mel Frequency Cepstral Coefficients (MFCC), is the method used to extract features from music signals and comparing suaru with unknown speakers with the existing speakers in the database. This application input data undergo several processes, before finally producing the key (Cord) tone. These processes include identifying the sound of the song. Voice recognition is useful for biometric authentication and communication between the computer system. Keywords: mel-frequency cepstral coefficients, vector quantization, K-means, tone, onset, humming.